2019
DOI: 10.1021/acschembio.9b00365
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Bypass of DNA–Protein and DNA–Peptide Conjugates by T7 RNA Polymerase

Abstract: DNA−protein cross-links (DPCs) are unusually bulky DNA adducts that block the access of proteins to DNA and interfere with gene expression, replication, and repair. We previously described DPC formation at the N7guanine position of DNA in human cells treated with antitumor nitrogen mustards and platinum compounds and have shown that DPCs can form endogenously at DNA epigenetic mark 5-formyl-dC. However, insufficient information is available about the effects of these structurally distinct DPCs on transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…It has even been reported that DPCs is a molecular marker of FA-related cancer risk [11,25]. DPCs are necessary for DNA replication, transcription, and cell growth in normal cells; however, excessive DPCs produced by endogenous and exogenous agents block DNA replication cause genomic instability and tumorigenesis [26][27][28]. In this study, the degree of genotoxicity in BMSCs exposed to FA was studied by detecting the levels of DNA breakage, DPCs, and micronucleus formation.…”
Section: Discussionmentioning
confidence: 98%
“…It has even been reported that DPCs is a molecular marker of FA-related cancer risk [11,25]. DPCs are necessary for DNA replication, transcription, and cell growth in normal cells; however, excessive DPCs produced by endogenous and exogenous agents block DNA replication cause genomic instability and tumorigenesis [26][27][28]. In this study, the degree of genotoxicity in BMSCs exposed to FA was studied by detecting the levels of DNA breakage, DPCs, and micronucleus formation.…”
Section: Discussionmentioning
confidence: 98%
“…TLS polymerases have been shown to bypass a GSHbased adduct (52,69,70) and (N-terminal-linked) peptides as long as 5-and 12-mers (71-73) but not a 23-mer peptide or green fluorescent protein (72). In vitro studies, including some in cells, have shown the mutagenic bypass of DNA-peptide cross-link by TLS polymerases (11,42,74). It is important to know how a DNA polymerase can bypass each cross-linked peptide entity and potentially cause base-pair mutations.…”
Section: Discussionmentioning
confidence: 99%
“…These super-bulky adducts can be generated by exposure of cells to endogenous and exogenous cross-linking agents (Stingele et al, 2017;Zhang et al, 2020). The presence of protein covalently attached to DNA strongly interferes with DNA replication, transcription, repair, and chromatin remodeling (Kuo et al, 2007;Klages-Mundt and Li, 2017;Yudkina et al, 2018;Ji et al, 2019). DPCs may be classified into five types, according to the nature of the covalent link in the DNA-protein complex and the presence of DNA strand breaks (Ide et al, 2015(Ide et al, , 2018Nakano et al, 2017).…”
Section: Introductionmentioning
confidence: 99%